2003
DOI: 10.1175/1520-0442(2003)016<1739:sritta>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Stratiform Rain in the Tropics as Seen by the TRMM Precipitation Radar*

Abstract: Across the Tropics (20ЊN-20ЊS), the Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (PR) indicates that for reflectivities Ն17 dBZ, stratiform precipitation accounts for 73% of the area covered by rain and 40% of the total rain amount over a 3-yr period (1998-2000). The ratio of the convective rain rate to the stratiform rain rate is 4.1 on average at the horizontal resolution of the PR data. Convective rain rates remain constant or decrease as the stratiform contribution to total rain increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
399
5
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 446 publications
(449 citation statements)
references
References 64 publications
(72 reference statements)
41
399
5
4
Order By: Relevance
“…It is the main process contributing to low rates of precipitation (less than 10 mm/day), but the distribution of heavy tropical precipitation is primarily due to large-scale precipitation. It should be noted that the dominance of large-scale precipitation over convective precipitation at high rainfall rates is completely counter to observations (Schumacher and Houze, 2003). The impact of horizontal resolution on precipitation extremes is manifested primarily by its effects on large-scale precipitation.…”
mentioning
confidence: 82%
“…It is the main process contributing to low rates of precipitation (less than 10 mm/day), but the distribution of heavy tropical precipitation is primarily due to large-scale precipitation. It should be noted that the dominance of large-scale precipitation over convective precipitation at high rainfall rates is completely counter to observations (Schumacher and Houze, 2003). The impact of horizontal resolution on precipitation extremes is manifested primarily by its effects on large-scale precipitation.…”
mentioning
confidence: 82%
“…Williamson (2008) argues that this may be a weak premise. Given that the horizontal scale of convection is on the order of 10 km (Schumacher and Houze, 2003), convection should be occurring at the sub-grid scale in all of the simulations presented in this manuscript. Therefore, increasing resolution should not increase the amount of resolved convection in any of these simulations.…”
Section: Size Distribution and Resolved Fractionmentioning
confidence: 99%
“…Therefore, increasing resolution should not increase the amount of resolved convection in any of these simulations. A properly scale-aware convection formulation should produce a consistent fraction of the total precipitation, roughly 20% according to Schumacher and Houze (2003), for any climate simulation with a horizontal resolution larger than approximately 10 km.…”
Section: Size Distribution and Resolved Fractionmentioning
confidence: 99%
“…We expect the benefits of having such a high-resolution dataset to outweigh the disadvantage of some statistical fluctuations since the horizontal gradients and temporal scale of precipitation over this region during the monsoon season, are probably much larger than the sampling errors (Anders et al, 2006;Romatschke and Houze, 2011). Also Schumacher and Houze (2003) and Bell and Kundu (2000) have suggested that 0.6 m/year rain accumulation threshold gives less noisy results. Most of the In dian region except the western most part of India receives more than 0.6 m/year (Pokhrel and Sikka, 2013).…”
Section: Trmm Dataset and Its Processingmentioning
confidence: 98%
“…The ''other'' category represents either noise or regions of precipitation aloft with no precipitation near the surface. The ambiguity of the ''other'' category and its very small contribution to total rainfall, implies that we can neglect "others" as was done by Schumacher and Houze (2003). further details of the PR 2A23 algorithm are available online at http://daac.gsfc.nasa.gov/.…”
Section: Trmm Dataset and Its Processingmentioning
confidence: 99%